Flight dreams : a life in the midwestern landscape - Knopp, Lisa, 1956- (Singular lives., 1998)
"When I was eleven the world was filled with birds, "writes Lisa Knopp of her girlhood in Burlington, Iowa. Picking up where she left off in her first book, Field of Vision, Knopp knits together sections of her life story through a pattern of images drawn from nature. The most prevalent of these unifying themes are metaphors of flight--birds, wind, moving upward and outward and across the midwestern landscape from Nebraska and Iowa to southern Illinois. Reminiscent of Thoreau's introspective nature writing and Dillard's taut, personal prose, each chapter in Flight Dreams stands alone as a distinct narrative, yet each is linked by profoundly personal descriptions of dreams, the natural world, defining experiences, and chance encounters with people that later prove to be fateful. Part Eastern meditation, part dream sequence, part historical reconstruction, Flight Dreams testifies to a deep understanding of how the natural world--its visible and invisible elements--guides our destinies